There's a place for people with disabilities within the arts: Exploring how interaction with the performing arts may facilitate the social and economic inclusion of youth with disabilities - Le Roux, Marlene (Division of Disability Studies, 2019)
This study aims to explore how interaction with the performing arts could facilitate the participation of youths with disabilities in opportunities for social and economic inclusion. Equal access for all is a dream, as the world is still a disabling place, particularly for women, poor, Black and persons with a disability. As a result of this intersectionality of social identities and oppression, a lack of access to mainstream activities and opportunities remains a day-to-day reality for many persons with disabilities (Le Roux, 2015). Persons with disability yearn for the individual freedoms enjoyed by most other members of society. One vehicle through which people with disabilities can further enrich themselves are through cultural and arts events. The 2006 United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) universally recognised the right of people with disabilities to: ● Access work opportunities (Article 27); and ● Take part in cultural life with others (Article 30), i.e., ensuring that people with disabilities have adequate access to these activities. This study aims to explore how youth with disabilities’ exposure to theatre performance, visiting the theatre or attending a workshop can derive benefit regarding their awareness and prospects for social and economic inclusion. The objectives of this study are to: 1. Describe the experience of youth with disabilities attending a performance at Artscape. 2. Describe how being at Artscape influences or expands career aspirations of youth with disabilities related to economic and social inclusion. 3. Describe the social and life skills learned through attending a performance or visiting Artscape as a facility. 4. Identify factors that influence the participation of youth with disabilities in attending performances and events at Artscape. 5. Investigate how participation in performing arts contributes to their social and economic inclusion. This study used a qualitative research approach, using critical ethnography methodology. Primary data was obtained from an in-depth interview with a young, Black disabled woman and three focus group discussions of six participants. Secondary data in the form of questionnaires were quantitatively analysed This research revealed that transport remains a major challenge for disabled youth seeking to interact with the arts. While disability is diverse and each disability is unique in itself, contact with the arts has been found to facilitate social and economic inclusion and trigger the empowerment of these youth. This was seen in the four themes that came out of the findings namely; Blown away, I can do it, you can do it, Embracing Hope, and a long way to go. Hence, accessibility has varying meanings for different kinds of disability. There remains a huge gap for people with disabilities to be included in social and economic activities, and as a result, youth with disabilities are still trapped in a world of exclusion. I have therefore proposed an Inclusive Model of Disability for Social and Economic inclusion, which are based on the same four themes that I derived from the findings, as well as a fifth theme entitled; Toward social and Economic Inclusion. Based on this model I have also discussed what the findings have shown under four themes; Artscape as a catalyst for inclusion, Career Aspirations, Social and Life Skills, and Enabling Social and Economic Participation. This study concludes that potential exists for disability inclusion and participation in the performing arts, and refers to numerous implications for the education, livelihoods, social and empowerment sectors to consider based on the CBR components of inclusive development, as well as some recommendations beyond Artscape.